Developing and Deploying a Hypertension Remote Patient Monitoring Program 101 - Musab S. Hommos, MBBS; Praneetha Elugunti, MHA, MBA; Amanda M. Pullee, DNP; Clay W. Walker, PA-C; Karen S. Drechsel, DNP; Stephanie R. Pinello, MSN; Andrea Fillers, MSN; Nandita Khera, MD, MPH; Margaret M. Paul, PhD, MS (Mayo Clinic Proceedings: Innovations, Quality & Outcomes)
Objective: To describe the development and deployment of a remote patient monitoring (RPM) program for hypertension and to share outcomes from an initial cohort of patients enrolled in this program. Patients and Methods: The development of an RPM program for hypertension is described in detail. A sample of patients who were enrolled in RPM, participated for at least 2 weeks, and completed the program from January 1, 2023, to December 31, 2023, were included in the analysis. Clinical data were summarized using descriptive statistics. For comparing continuous variables, the independent samples t test was employed. For analyzing relationships between categorical variables, the χ2 test was utilized. Results: Total of 101 patients met the inclusion criteria. The median age was 69 years with a range from 22 to 95 years; 51 (51%) were men, 93 (92%) were White, and 6 (6%) identified as Hispanic. The median length of participation in the program was 38 days, with a range from 18 to 160 days. The average blood pressure decreased during program enrollment from 153/84 to 126/75 mm Hg (P<.001), whereas heart rate decreased from 73 to 70 bpm (P=.03). On average, the number of antihypertensive drugs increased from 2.06 to 2.3 (P=.02). On average, clinicians received 1.1 messages per week per enrolled patient in RPM. Conclusion: Developing and implementing an RPM program for hypertension is feasible with adequate resources, planning, and piloting. These programs are associated with clinically significant improvements in blood pressure control for patients with hypertension without considerably increasing calls and messages from patients beyond routine care.